1995
DOI: 10.1111/j.1365-2141.1995.tb08412.x
|View full text |Cite
|
Sign up to set email alerts
|

Needle liver biopsy in thalassaemia: analyses of diagnostic accuracy and safety in 1184 consecutive biopsies

Abstract: We report the reliability and safety of percutaneous liver biopsy in the evaluation of hepatic iron loading and histology in patients with homozygous /3thalassaemia prior to and in serial biopsies following allogeneic bone marrow transplantation for this disorder. 501 thalassaemic patients aged 11 + 4.5 years (range 1-32

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 16 publications
3
78
0
7
Order By: Relevance
“…These two parameters are reported in the literature to adequately reflect iron load, 22,24 and in our survey reveal a strong correlation, as defined by the Spearman's test. In fact, calculation of the coefficient of determination (R2) showed that LIC correlated with SF (R2=0.417, p<0.001).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…These two parameters are reported in the literature to adequately reflect iron load, 22,24 and in our survey reveal a strong correlation, as defined by the Spearman's test. In fact, calculation of the coefficient of determination (R2) showed that LIC correlated with SF (R2=0.417, p<0.001).…”
Section: Resultssupporting
confidence: 77%
“…Only liver samples with a dry weight of at least 1 mg were considered for the present study. 22,24 Mean value of dry weight liver biopsies was 2.34 mg (range: 1.06-4.58 mg). SF levels were determined by standard methods during routine blood testing prior to transplant on all the 97 patients.…”
Section: Clinical Parametersmentioning
confidence: 99%
“…The second condition is that the liver-biopsy specimen is adequate, 1 mg dry weight; variability increases with smaller samples. No complications were observed with liver biopsy, extending the record of safety of liver biopsy in expert hands [3][4][5]. These results corroborate previous observations from these and other investigators [5][6][7] that support chemical measurement of the iron concentration in a liver-biopsy specimen as the reference standard for measurement of the hepatic iron concentration.…”
supporting
confidence: 86%
“…This analysis was conducted after a large in house liver biopsy experience [10] and evidence coming from another study demonstrating not increasing complication rate when one, two, or three specimens are taken [11]. We have already demonstrated that liver iron concentration is predictive of the entire body iron store in patients with thalassemia [6].…”
Section: Discussionmentioning
confidence: 99%